Management of Corrective and Preventive Аctions - Abdurahmonovich, Mamajonov Abduvoxid; Ulugbekovich, Kuldashev Jahongir (International Journal on Orange Technologies, 2022)
This article discusses the requirements of international and organizational standards for the correction, identification and prevention of inconsistencies identified in audits of management systems.